2018
DOI: 10.1136/bmjsem-2017-000311
|View full text |Cite
|
Sign up to set email alerts
|

Association between frontal plane knee control and lower extremity injuries: a prospective study on young team sport athletes

Abstract: Background/aimPoor frontal plane knee control can manifest as increased dynamic knee valgus during athletic tasks. The purpose of this study was to investigate the association between frontal plane knee control and the risk of acute lower extremity injuries. In addition, we wanted to study if the single-leg squat (SLS) test can be used as a screening tool to identify athletes with an increased injury risk.MethodsA total of 306 basketball and floorball players participated in the baseline SLS test and a 12-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 45 publications
1
46
0
1
Order By: Relevance
“…In the current study, we found no association between the FPKPA during the SLS and future lower extremity injuries. In our previous study among older team sport athletes (mean age 15.7 ± 1.8 years), we detected a significant association between FPKPA and acute lower extremity injury and acute ankle injury: Displaying high FPKPA was associated with a higher odds of injury . The association between frontal plane knee control and the risk of injuries has not been previously studied in young, under 14‐year‐old athletes.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In the current study, we found no association between the FPKPA during the SLS and future lower extremity injuries. In our previous study among older team sport athletes (mean age 15.7 ± 1.8 years), we detected a significant association between FPKPA and acute lower extremity injury and acute ankle injury: Displaying high FPKPA was associated with a higher odds of injury . The association between frontal plane knee control and the risk of injuries has not been previously studied in young, under 14‐year‐old athletes.…”
Section: Discussionmentioning
confidence: 76%
“…The visual assessment of frontal plane knee control correlates well with the FPKPA, when assessment if performed by experienced observer. 30 Previous studies on young athletes have shown that reduced frontal plane knee control is associated with higher risk of future injuries, 29,39,44,45 although all the studies are not in agreement. 46 As reduced knee control has been identified as an injury risk factor, using movement control tests to identify athletes who could reduce their injury risk by improving knee control seems sensible.…”
Section: The Single-leg Squat Testmentioning
confidence: 97%
See 2 more Smart Citations
“…Knee valgus loading, high vertical ground reaction force as well as limited knee and hip flexion during a vertical drop jump task have been associated with ACL injury risk in young female athletes. A recent study suggested association between excessive knee valgus during a single‐leg squat and a risk of LE injuries as well as ankle injuries . Furthermore, a combination of knee valgus and lateral trunk motion during a single‐leg drop jump has been suggested being associated with increased risk of non‐contact knee injuries .…”
Section: Introductionmentioning
confidence: 99%